2016
DOI: 10.1093/neuonc/now044
|View full text |Cite
|
Sign up to set email alerts
|

MiR-301a is activated by the Wnt/β-catenin pathway and promotes glioma cell invasion by suppressing SEPT7

Abstract: Our findings revealed the mechanism of action for miR-301a in tumor cell invasion. Moreover, the Wnt/miR-301a/SEPT7 signaling axis might be a novel target in treating glioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 29 publications
2
36
0
1
Order By: Relevance
“…Another possible pathway promoting cell growth upon GOLPH3 overexpression is the GOLPH3-Wls-Wnt axis [67]. As said above, GOLPH3 interacts with the VPS35 retromer protein [9] and Wnt/β-catenin [68,69], and consequently, Wntless (Wls, the chaperone protein of Wnt secretion) [70] are important in glioma etiology. Lu and collaborators [67] have recently demonstrated that GOLPH3 affects Wls recycling, and consequently Wnt secretion and function, promoting tumorigenesis [3].…”
Section: Golph3 Deregulation and Brain Tumorsmentioning
confidence: 97%
“…Another possible pathway promoting cell growth upon GOLPH3 overexpression is the GOLPH3-Wls-Wnt axis [67]. As said above, GOLPH3 interacts with the VPS35 retromer protein [9] and Wnt/β-catenin [68,69], and consequently, Wntless (Wls, the chaperone protein of Wnt secretion) [70] are important in glioma etiology. Lu and collaborators [67] have recently demonstrated that GOLPH3 affects Wls recycling, and consequently Wnt secretion and function, promoting tumorigenesis [3].…”
Section: Golph3 Deregulation and Brain Tumorsmentioning
confidence: 97%
“…Wang, Wang, Han, et al, 2013;Z. Wang, Dai, et al, 2015;Yue et al, 2016). Recently, Fang, Li, Xu, Hui, and Li (2018)…”
Section: Suppressive Roles Of Wnt/ β-Catenin Pathway In Glioma Devementioning
confidence: 99%
“…They also observed that the serum exosomal miR-301a levels were lower after surgical resection of the tumour, but were increased during GBM recurrence, indicating that serum exosomal miR-301a could be a potential biomarker for diagnosis/prognosis for GBM patients. 127,128 Ebrahimkhani et al 129 used a panel of seven exosomal miRNAs-miR-182-5p, miR-328-3p, miR-339-5p, miR-340-5p, miR-485-3p, miR-486-5p and miR-543-to differentiate GBM patients from healthy controls with an accuracy rate of 91.7%. In addition, Santangelo et al 91 analysed a miRNA signature in exosomes from the serum of glioma patients in an attempt to differentiate tumour grading and gliomas from brain metastases.…”
Section: Microvesicles In Glioblastomamentioning
confidence: 99%